Beer : tap into the art and science of brewing - Bamforth, Charles W., 1952- (Oxford University Press, 2003)
Charles Bamforth, who has been described as "one of the two or three brewing scientists of his generation," here gives us a revised and updated version of his definitive guide to brewing. Bamforth traces the history of beer from ancient Babylon some 8,000 years ago to today's brewing science, recounting important brewing milestones along the way. This new edition contains expansive coverage of global beer styles throughout the world, the sensory character of beer flavor, and the development of the global brewing industry. Each of the staples of brewing (barley, hops, water, and yeast), the fundamental processes of brewing (mashing, boiling, fermentation, maturation, and packaging), and the quality determinants (flavor, foam, color, and clarity) is covered in comprehensive detail. Never losing sight of the central role of science in beer's design and manufacture, Bamforth closes with some predictions about the future of the industry. Ideal for the beer lover, amateur brewer, hobbyist, and undergraduate alike, The Art and Science of Brewing Beer is the ideal one-volume handbook on brewing beer.